PENGARUH PROFITABILITAS, SOLVABILITAS, TATA KELOLA PERUSAHAAN, DAN AUDIT QUALITY TERHADAP AUDIT REPORT LAG PADA MASA PANDEMI DAN ENDEMI COVID-19 DI INDONESIA - Davin Hansel Chaindrakarsa; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of profitability, solvency, corporate governance which includes ownership concentration, audit committee, and the number of audit committee meetings, and audit quality which includes audit opinion and the reputation of the Public Accounting Firm (PAF) on audit report lag. In this study, the variables of profitability, solvency, ownership concentration, audit committee, number of audit committee meetings, audit opinion, and PAF reputation act as independent variables, while audit report lag serves as the dependent variable. The sample in this study consists of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period, totalling 148 samples. The sample selection was based on a purposive sampling method using criteria and requirements determined by the researcher. The testing and analysis methods used in this study include descriptive statistical analysis and statistical hypothesis testing using the Partial Least Squares (PLS) method through the WarpPLS 8.0 application. The results of the study show that not all research variables have a statistically significant effect on audit report lag, and the influence is not consistently distributed. The variables that consistently affect audit report lag in both pandemic and endemic Covid-19 situations are solvency, number of audit committee meetings, and audit opinion.